Students multicultural awareness of Aceh dormitory in Yogyakarta - Lailatul Hikmah; Suharno Suharno (Jurnal Civics: Media Kajian Kewarganegaraan)
Several provinces in Indonesia have regional dormitories in Yogyakarta. This allows each student from various regions to have awareness of their respective ethnic identities, even though this has the potential to create horizontal conflicts. This study aims to describe how Aceh dormitory students in the city of Yogyakarta interpret ethnic identity and how intercultural communication relationships with other ethnicities and the surrounding community and how their views are related to the disintegration of the nation. This research is qualitative research using data collection techniques through interviews. The results showed that Acehnese students were aware of the ethnic identity that was the basis of the hostel and they saw that ethnic identity was important. Aceh dormitory students also introduce culture in cultural events, through which intercultural communication with other ethnicities and the surrounding community can be established. They think that as sons and daughters of the region, they should be proud of their respective ethnicities, but still have to uphold an attitude of inter-ethnic tolerance, so that this awareness does not cause the nation's disintegration.